Systematic mediastinal lymph node dissection outcomes and conversion rates of uniportal video‐assisted thoracoscopic lobectomy for lung cancer. Issue 9 (23rd July 2019) - Wu, Han‐Ran; Liu, Chang‐Qing; Xu, Mei‐Qing; Xu, Guang‐Wen; Xiong, Ran; Li, Cai‐Wei; Xie, Ming‐Ran
Abstract : Background: To evaluate the systematic mediastinal lymph node (LN) dissection outcomes and conversion rates of uniportal video‐assisted thoracoscopic surgery (UVATS). Methods: Patients with non‐small‐cell lung cancer who underwent video‐assisted thoracoscopic surgery (VATS) and systematic mediastinal LN dissection between January 2015 and January 2017 were retrospectively reviewed. We categorized the patients into two groups according to the different surgical approaches. Patients' clinical data were collected and compared. The index of estimated benefit from LN dissection was used to evaluate the therapeutic value of LN dissection for each station. Results: A total of 453 patients underwent VATS, including 197 patients in the UVATS group and 256 patients in the triportal VATS (TVATS) group. There were no significant differences in the 1‐, 2‐ and 3‐year survival rates of these two groups ( P > 0.05). There were no statistically significant differences in the operative time, numbers and stations of LNs, numbers and stations of N2 LNs, conversion rate or postoperative complications. The UVATS group had less intraoperative blood loss, a shorter duration of hospital stay, less chest tube drainage and a shorter duration of chest tube drainage than the TVATS group ( P < 0.05). The conversion rates in the UVATS and TVATS groups were 5.1% and 4.3%, respectively, and the difference was not significant. The same degree of LN sampling was achieved in both groups. Conclusion: UVATS permits the same degree of LN sampling as TVATS without a difference in the conversion rate. Abstract : >This study was performed to evaluate the systemic mediastinum lymph node dissection and conversive rate in uniportal video‐assisted thoracoscopic lobectomy for the treatment of non‐small‐cell lung cancer compared with three‐port video‐assisted thoracoscopic lobectomy, and the lymph node dissection of uniportal video‐assisted thoracoscopic lobectomy was the same as that of triportal video‐assisted thoracoscopic lobectomy, and there was no difference in the conversive rate.